Understanding Prognostic Factors for Human Papillomavirus Vaccination: A Rural Community Case–Control Study - Lara Colomé-Ceballos; Josep Lluís Clua-Espuny; Concepción Ceballos-García; Josep Clua-Queralt; Maria Jesús Pla-Farnós; José Fernández-Sáez (Vaccines, 2023)
HPV vaccination coverage rates can vary depending on several factors. The main objective of this study is to identify possible independent prognostic factors that have an impact on HPV vaccination in a rural community, specifically related to sexual and reproductive health. A case–control, retrospective, community-based study was carried out on women aged 15 to 40 in the primary health centers of Southern Catalonia’s Terres de l’Ebre region, Spain, from 1 January 2020 to 31 December 2022. A random sample of 520 women with an average age of 29.3 (SD 7.8) years old was included in the study. Independent prognostic factors: age OR 0.680 (95% CI: 0.635–0.729, p < 0.001), immigrant origin OR 0.215 (95% CI: 0.109–0.422, p < 0.001), and HPV PCR OR 7.402 (95% CI: 2.504–21.880, p < 0.001). The variables that showed a barrier effect for HPV vaccination were age (OR 0.680, 95% CI 0.635–0.729, p < 0.001), and immigrant origin (OR 0.215, 95% CI 0.109–0.422, p < 0.001). The variable that showed a facilitating effect for HPV vaccination was HPV PCR (OR 7.402, 95% CI 2.504–21.880, p < 0.001).